Spatial analysis of residential load growth due to electric vehicle recharge - Morro-Mello, I. [UNESP]; Freitas, A. B.; Melo, J. D.; Padilha-Feltrin, A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
The estimation of load curves by class of consumers is an information used in several studies of planning and operation of electrical distribution networks. The recharging of electric vehicles can modify these curves by increasing the maximum demand. Due to the high prices of electric vehicles, the spatial distribution of households with electric vehicles will be heterogeneous. In order to identify the regions where the load curve may suffer a greater change and quantify the increase in the demand of the residential sector, a methodology that characterizes spatially the socioeconomic information is presented. This methodology is composed of 3 modules to: identify households with favorable conditions for the purchase of electric vehicles; calculate the battery state of charge in the start loading and determine load curves of the residential sector considering the charging of electric vehicles. The determined values by each module are represented in heat maps in order to identify regions that may have a greater impact on the distribution system. The proposal is tested in a Brazilian city to identify the regions that will have a major change in the daily load curve of the residential sector.
Keywords: Electric vehicle; Load curve; Power system planning; Spatial analysis; Transportation system